Controllable Synthesis of Calcium Carbonate with Different Morphologies and Phases Assisted by F127 - Rong, Xueliang; Yang, Ming; Huang, Qiao; Zhao, Pin (Asian Journal of Chemistry, 2014)
Spica-like vaterite and nanorod-bundles aragonite have been synthesized through a precipitation route assisted by triblock copolymer EO106PO70EO106 (F127). The as-prepared CaCO3 samples are characterized by X-ray powder diffraction, scanning electron microscopy and high-resolution transmission electron microscopy. The effect of copolymer on the morphologies of CaCO3 samples is investigated by SEM, compared with the products obtained without adding copolymer. The possible formation mechanism of the calcium carbonate with different morphologies was discussed. It was supposed that the copolymer F127 made the morphologies of calcium carbonate more uniform. The photoluminescence properties of CaCO3:Eu3+ red phosphors were also investigated.